Development and Evaluation of Virtual Learning Environment For Learning Selected Technical Drawing Concept In Ilorin Metropolis - Gboyega Ayodeji Aladesusi; Temitayo Omolara Onasanya; Adenubi Samuel Onasanya (Universitas Islam Negeri (UIN) Sulthan Thaha Saifuddin Jambi, 2020)
ABSTRACT This study developed and evaluate Virtual Learning Environment for learning selected technical drawing concept in Ilorin metropolis. The study employed the use of design and development research of model type using the significant learning-integrated course design model. The sample size of the participants was five (5) Educational Technology experts and five (5) mechanical Engineering experts. This gave a total sample size of ten (10). Three research instruments were used in this study (i) developed Virtual Learning Environment (VLE), (ii) Educational Technology expert’s questionnaire (EEQ) and (iii) Mechanical Engineering expert’s questionnaire (MEEQ). The instruments were validated by experts. The reliability of the instruments was obtained using Cronbach alpha formula which yielded 0.76 coefficient. Four research questions were raised and answered. Findings revealed that educational technology experts and Mechanical Engineering expert rated the developed virtual learning environment high and effective for learning Technical drawing. However, the benefits of the virtual learning environments are unquantifiable and incomparable with the cost. The study recommended that provision of necessary technological facilities should be made by the government and private owners to schools in order to be able to implement and promote further use of technology in education.